Pengaruh Daya Tarik, Fasilitas Dan Aksesibilitas Terhadap Keputusan Berkunjung Ke Objek Wisata Gunung Kelud Di Kecamatan Ngancar Kabupaten Kediri - Bagus Cahyo Nugroho (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to determine the influence of the variables of attraction, facilities and accessibility on the decision to visit (Y) at the Mount Kelud tourist attraction in Ngancar sub-district, Kediri regency. This type of research is quantitative research. The number of samples in the research obtained was 392 respondents. This research data was obtained through questionnaires, interviews and literature studies. The sampling technique in this research used Accidental Sampling. Data sources were obtained from primary and secondary data. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The research results showed that the t test result of the attraction force variable had a partially significant effect on the decision to visit. The facility variable has a partially significant effect on the decision to visit. The accessibility variable has a partially significant effect on the decision to visit. The results of the F test show that attractiveness, facilities and accessibility have a positive and significant effect simultaneously on the decision to visit (Y). The suggestion for this research is that tourist attractions should pay more attention to the things that influence the decision to visit.